Efektivitas Pemberian Air Rebusan Daun Salam dan Daun Kelor terhadap Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi di PMB Eni Lestari, S.Tr.,Keb BEKASI - Apriyana, Diyanti Nur; Jusmawati, Jusmawati (Universitas Malahayati, 2025)
ABSTRACT Lowering blood pressure can be done using herbal therapy, namely by giving boiled water from bay leaves and boiled water from Moringa leaves. Based on the above, the author is interested in conducting research entitled